Age-Dependent Neurogenesis and Neuron Numbers within the Olfactory Bulb and Hippocampus of Homing Pigeons - Meskenaite, Virginia; Krackow, Sven; Lipp, Hans-Peter (Frontiers in Behavioral Neuroscience, 2016)
Many birds are supreme long-distance navigators that develop their navigational ability in the first months after fledgling but update the memorized environmental information needed for navigation also later in life. We studied the extent of juvenile and adult neurogenesis that could provide such age-related plasticity in brain regions known to mediate different mechanisms of pigeon homing: the olfactory bulb, and the triangular area of the hippocampal formation. Newly generated neurons (visualized by doublecortin, DCX) and mature neurons were counted stereologically in 35 pigeon brains ranging from 1 to 168 months of age. At the age of one month, both areas showed maximal proportions of DCX positive neurons, which rapidly declined during the first year of life. In the olfactory bulb, the number of DCX-positive periglomerular neurons declined further over time, but the number of mature periglomerular cells appeared unchanged. In the hippocampus, the proportion of DCX-positive neurons showed a similar decline yet to a lesser extent. Remarkably, in the triangular area of the hippocampus, the oldest birds showed nearly twice the number of neurons as compared to young adult pigeons, suggesting that adult born neurons in these regions expanded the local circuitry even in aged birds. This increase might reflect navigational experience and, possibly, expanded spatial memory. On the other hand, the decrease of juvenile neurons in the aging olfactory bulb without adding new circuitry might be related to the improved attachment to the loft characterizing adult and old pigeons.